Identification of sex-linked markers in the sexually cryptic coco de mer: are males and females produced in equal proportions? - Morgan, Emma J.; Kaiser-Bunbury, Christopher; Edwards, Peter J.; Scharmann, Mathias; Widmer, Alex; Fleischer-Dogley, Frauke; Kettle, Christopher J. (Oxford University Press, 2020)
Lodoicea maldivica (coco de mer) is a long-lived dioecious palm in which male and female plants are visually indistinguishable when immature, only becoming sexually dimorphic as adults, which in natural forest can take as much as 50 years. Most adult populations in the Seychelles exhibit biased sex ratios, but it is unknown whether this is due to different proportions of male and female plants being produced or to differential mortality. In this study, we developed sex-linked markers in Lodoicea using ddRAD sequencing, enabling us to reliably determine the gender of immature individuals. We screened 589 immature individuals to explore sex ratios across life stages in Lodoicea. The two sex-specific markers resulted in the amplification of male-specific bands (Lm123977 at 405 bp and Lm435135 at 130 bp). Our study of four sub-populations of Lodoicea on the islands of Praslin and Curieuse revealed that the two sexes were produced in approximately equal numbers, with no significant deviation from a 1:1 ratio before the adult stage. We conclude that sex in Lodoicea is genetically determined, suggesting that Lodoicea has a chromosomal sex determination system in which males are the heterogametic sex (XY) and females are homogametic (XX). We discuss the potential causes for observed biased sex ratios in adult populations, and the implications of our results for the life history, ecology and conservation management of Lodoicea.